TINJAUAN YURIDIS KORUPSI KEBIJAKAN DALAM PENGADAAN BARANG DAN JASA PADA LINGKUP INSTANSI PEMERINTAH DAERAH DI ERA DIGITAL - Andhika Abdillah (LP3M, 2024)
This research aims to conduct a juridical review of policies in the procurement of goods and services within local government agencies in the digital era, with a special focus on efforts to prevent and overcome corruption. Procurement of goods and services is one of the areas vulnerable to corrupt practices in the public sector. In this context, the digital era provides new challenges and opportunities in the implementation of goods and services procurement policies to reduce the risk of corruption. This research methodology uses a normative and descriptive juridical approach to analyze various laws, policies, and practices related to the procurement of goods and services in local government agencies. In addition, this research also involves a literature study to understand the latest trends and developments in public procurement in the digital era. The results show that public procurement within local government agencies faces various challenges, especially related to the risk of corruption. Corrupt practices in public procurement can include collusion between government officials and private parties, nepotism in the vendor selection process, and falsification of documents to win contracts. Therefore, effective legal and policy protections are essential to prevent and mitigate corruption in public procurement. In the digital age, information and communication technology offers a range of solutions to improve transparency, accountability, and efficiency in public procurement. Electronic procurement systems, e-procurement platforms and blockchain technology are some examples of tools that can be used to reduce the risk of corruption in public procurement. However, the implementation of digital technologies can also bring new challenges, such as the need for stricter data security and adequate training for stakeholders. The study also highlights the important role of oversight agencies, such as the Financial and Development Supervisory Agency (BPKP) and the Corruption Eradication Commission (KPK), in monitoring public procurement in local government agencies. By improving the capacity and independence of oversight agencies, as well as strengthening cooperation between the government, private sector and civil society, efforts to prevent and counter corruption in public procurement can be more effective. This study concludes that procurement of goods and services within local government agencies in the digital era requires a holistic approach that involves the active role of various stakeholders. Effective legal and policy protections, wise application of digital technology, and strict supervision from oversight institutions are key to preventing and combating corruption in public procurement in the digital era